Multinational Business Finance / Seventh Edition - Eiteman David K; Moffett Michael H; Stonehill Arthur I (Addison-Wesley Publishing Company, 1995)
The International Financial Environment, Introduction to Multinational Business Finance, The International Monetary System, Balances and Imbalances of Payments, Foreign Exchange Markets, The Foreign Exchange Market, Interantional Parity Conditions, Foreign Currency Options, Managing Foreign Exchange Exposure, Transaction Exposure: Measurement and Management, Operating Exposure, Accounting Exposure, Financing from a Global Perspective, Internationalizing the Cost of Capital, Designing the Financial Structure, Sourcing Equity Internationally, Sourcing Debt Internationally, Interest Rate Risk Management, Trade Financing, International Banking, Import and Export Financing, Foreign Investment Decisions, Corporate Strategy and Foreign Investment, Political Risk Management, Multinational Capital Budgeting, International Portfolio Investments, Controlling International Operations, Principles of Multinational Taxation, Working Capital Management, Advanced Topics in Currency Risk Management.
The International Financial Environment, Introduction to Multinational Business Finance, The International Monetary System, Balances and Imbalances of Payments, Foreign Exchange Markets, The Foreign Exchange Market, Interantional Parity Conditions, Foreign Currency Options, Managing Foreign Exchange Exposure, Transaction Exposure: Measurement and Management, Operating Exposure, Accounting Exposure, Financing from a Global Perspective, Internationalizing the Cost of Capital, Designing the Financial Structure, Sourcing Equity Internationally, Sourcing Debt Internationally, Interest Rate Risk Management, Trade Financing, International Banking, Import and Export Financing, Foreign Investment Decisions, Corporate Strategy and Foreign Investment, Political Risk Management, Multinational Capital Budgeting, International Portfolio Investments, Controlling International Operations, Principles of Multinational Taxation, Working Capital Management, Advanced Topics in Currency Risk Management.